Cronotopia romântica: o jogo espaço-tempo em Noite na taverna, de Álvares de Azevedo - Mattiuz, Fernanda Remes (2018)
The present study proposes to discuss the temporal intertwining and its unfoldings in Night in the tavern (1855), of Álvares de Azevedo (1831-1852), with a view to identifying the space-time game and verifying how it articulates the narrative structure. To this end, the following theoretical contributions will be listed: Antonio Candido's article Education at night (1989), which supports the thesis on the continuity of Macário in the Night in the tavern; Forms of time and chronotope in the novel (essays of historical poetics), in which the concept of chronotope is worked by Mikhail Bakhtin (2014); and the binomial aesthetic, described by Azevedo himself in the critical preface to the second part of Lira dos vintes anos (1853). From these works, we expect to understand the artistic procedures used in the construction of time and space as indissoluble categories, as well as to raise discussions about the chronotope as a possible narrative constituent, responsible for linking one work to another, and also to contribute to the critical reading of azevedian prose